Autodesk Maya and Autodesk 3ds Max - Pardew, Les (Thomson Course Technology, 2007)
For artists and animators currently using either 3ds Max or Maya, this book outlines the scope of what each program can do and how they complement each other. These two programs dominate the 3D market and knowing how to use both programs allows you to increase your effectiveness as an artist. This tutorial-style book explains how to create the same model or animation using either program. Each chapter contains a project that is created by one artist in Maya and another artist in 3ds Max in a side-by-side comparison